2017
DOI: 10.1007/s00138-017-0898-3
|View full text |Cite
|
Sign up to set email alerts
|

Tracking using Numerous Anchor Points

Abstract: In this paper, an online adaptive model-free tracker is proposed to track single objects in video sequences to deal with real-world tracking challenges like low-resolution, object deformation, occlusion and motion blur. The novelty lies in the construction of a strong appearance model that captures features from the initialized bounding box and then are assembled into anchor point features. These features memorize the global pattern of the object and have an internal star graphlike structure. These features ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…It has been shown in [15] and [16] that structure can be a powerful appearance representation for visual object tracking. Whereas in [14], it has been shown that the structure of an object can help to tackle occlusion. Our motivation for using structure is inspired by the idea that by exploring the intrinsic structure of a target face may help to discover a particular pattern of a face of interest.…”
Section: Proposed Face Tracking Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been shown in [15] and [16] that structure can be a powerful appearance representation for visual object tracking. Whereas in [14], it has been shown that the structure of an object can help to tackle occlusion. Our motivation for using structure is inspired by the idea that by exploring the intrinsic structure of a target face may help to discover a particular pattern of a face of interest.…”
Section: Proposed Face Tracking Methodsmentioning
confidence: 99%
“…To adapt to the scale variation of the face, we use the same strategy, as used in [14]. The authors utilized pairwise distances between matched keypoints between consecutive frames to tackle scale change.…”
Section: Scale Adaptation and Computation Of Appearance Similarity Scmentioning
confidence: 99%
See 3 more Smart Citations